Dwa modele nacjonalizmu. Refleksje nad miejscem religii i Kościoła w koncepcjach Romana Dmowskiego i Dmytra Doncowa - Tomanek, Przemysław (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
In order to analyze the question of religion’s place in the conceptions of Roman Dmowski and Dmytro Doncov, the author selected works — usually written and published in the 1920s — which are representative in this respect. In his conclusions the author emphasizes that, in his texts devoted to the issues of religion and Church, Dmowski unequivocally appears as a propagator of the concept and model of Pole-Catholic, whereas in his political statements he approaches the position of religious integralism, seeing his political background as a force realizing the conceptions of political Catholicism. On the other hand, controversies and significant contradictions as far as the estimation of the role of religion and Church in the social life is concerned, which were observable in Doncov’s works, should be attributed to his doctrinal evolution: from socialism to its distinct negation, from anti-religious position to the apotheosis of military church and to the affirmation of explicitly conservative perspective. Doncov held the operating mode of the Catholic Church in high esteem and complimented the organizational structure of Roman Catholicism with the strong institution of papacy. At the same time he considered Russian Orthodoxy to be dangerous to the Ukrainian nation because — he claimed — it turns Ukrainians into slaves who adopt an attitude of silent humility toward the despotic government.
Keywords: katolicyzm; nacjonalizm; Dmowski, Roman (1864-1939); Doncow, Dmytro (1883-1973); religia